Comments on Martin Lybecker's Enhanced Corporate Governance - Mercer E. Bullard (Washington University Law Quarterly, 2005)
Martin Lybecker’s article, Enhanced Governance for Mutual Funds: A Flawed Concept that Deserves Serious Reconsideration, raises significant issues regarding the Securities and Exchange Commission’s (“Commission” or “SEC”) exercise of its exemptive authority. Under that authority, the Commission amended a number of exemptive rules under the Investment Company Act of 1940 (“’40 Act”) to require that mutual funds relying on those rules conform to enumerated governance practices (“fund governance reforms”). Lybecker argues that the fund governance reforms deserve serious reconsideration primarily because, in his opinion, they (1) were unauthorized, (2) were not adequately justified, and (3) will be of “questionable efficacy.” To the contrary, the Commission has ample authority to adopt the fund governance reforms, and the recent mutual fund scandal provided more than adequate justification for them. The Commission has broad exemptive authority under the ’40 Act, and the incorporation ofgovernance conditions into rules adopted under that authority mirrors the way in which Congress has used governance requirements in the Act. Both Congress and the Commission have long used governance requirements to protect investors, generally for the purpose of monitoring and managing conflicts of interest between funds and their sponsors. The recent mutual fund scandal confirmed the risks to shareholders presented by these conflicts of interest and accordingly provided more than adequate justification for strengthening the governance conditions in the exemptive rules. Whereas Lybecker is unpersuasive regarding the lack of authority and justification for the fund governance reforms, he may be correct that their efficacy is questionable. He essentially argues that the reforms will fail because independent directors lack the ability to serve in the watchdog capacity that the exemptive rules assign to them. It is hard to know the answer to the efficacy question, however, not only because it is inherently predictive, but also because the Commission has never explained exactly what it expects independent directors to do in the context of the exemptive rules. Indeed, Lybecker’s argument is partly that the Commission has failed to make the case as to its authority or the justification or efficacy of the reforms. The relevant proposing and adopting releases appear to base the fund governance reforms more on a general disagreement with Congress’s decisions—for example, not to require an independent fund chairman and to require only a forty percent independent board—than on the view that the reforms are necessary to protect investors specifically in the context of the exemptive rules into which the reforms have been incorporated. There is no evidence that the Commission knows whether the independent directors have been effective in the context of the operation of the exemptive rules in the past, or that it has any way of measuring their effectiveness in the future. The problem may be more serious, as there also is no evidence that the Commission knows if the exemptive rules themselves have been effective in protecting investors. Perhaps it is not the fund governance reforms alone that deserve serious reconsideration, but also the authority,
Keywords: Boards of directors; Conflicts of interest; Corporate governance; Mutual fund industry; Mutual fund managers; Mutual funds; Investment Company Act of 1940; Lybecker; Martin; Enhanced Corporate Governance; United States